Strategi Pengembangan Situs Manusia Purba Sangiran sebagai Daya Tarik Wisata Budaya - Enny Mulyantari (Media Wisata, 2016)
Tourism proved to contribute to the acceptance of local revenues and plays a role in alleviating poverty. Tourism also plays a role in efforts to improve the nation's identity and encourage awareness and community pride of the natural and cultural wealth. With tourism, a country or more specifically of local government where it is located will get revenue from the income of each tourism destination. Potential tourism attraction in Sangiran, Sragen has not been fully optimally managed, so that the existence of a tourism asset has not received the maximum response from visitors in the form of tourist visits.The problem in this research is how the potential of cultural tourism Sangiran site and what strategies are applied to the future development of Sangiran Site as a tour. This research aims to find the strategies in Sangiran tourism development according to the character as a world heritage site. This research uses SWOT analysis, to find strengths weaknesses factors, opportunities and challenges faced in the development of these attractions. This research is qualitative which look at research as a process, in order to gain a deep understanding with regard to community interaction in the area of research, Sangiran Site, Kalijambe, Sragen, Central Java Province.The results show that as rated the world's cultural heritage, tourism development positions Sangiran located in a strategic position if it is able to use optimally the power and opportunities that it has. One strength of tourist objects is because of the uniqueness and rarity, as shown by a collection of objects on display in the Museum of Ancient Man Sangiran. The cultural heritage objects, dating from prehistoric times, either in the form of early human fossils millions of years old, as well as other antique objects which the old is hundreds of years old is very important to understand the life of the ancestors of Indonesia in the past.Efforts to prevent the theft of Sangiran Site’s fossils, so in addition to the ongoing elucidation of the importance of cultural heritage, legal sanctions should be enforced, due to the exploitation of fossil violating Republic Act No. 11 the Year 2010 About the Cultural Heritage. Therefore, it is considered important and urgent, in order to be formed Awareness group as one component in society which have an important role and contribution in the development tourism of the Sangiran Site.